Grammar in Spoken Discourse: A Need Analysis of English Education Study Program Students - Septi Marlini; Wisma Yunita; Syahrial Syahrial (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
This research investigated the need analysis of Grammar in Spoken Discourse for the English Education Study Program. The objectives of this research were to find out: the current learning condition in teaching grammar at the English Education Study Program of University of Bengkulu and the needs for Grammar in Spoken Discourse course. This research used a mixed-method design. One hundred and fourteen students on fourth semester engaged as the correspondent of the questionnaire while four grammar lecturers were selected as the participant of interview. To gather the data, the questionnaire and interview were deployed and were further analyzed by using simple statistical of data analysis. The findings found that in the current conditions in learning grammar at English Education Study Program of University of Bengkulu already meet with the students’ needs in area of method, media and evaluation of learning. Then, Quantifier, Comparison, Form of Other, Stating Preference, How to Connect Ideas, Gerund, Infinitives, Modal Auxiliaries, Expressing Ability; Advice, Necessity, Requests, and Suggestions were materials needed for Grammar in Spoken Discourse course. There is difference between current learning situation and need analysis result for Grammar in Spoken Discourse in the context of material. The material prepares more contextual. Text which is related to the topic material of learning was prepared in order to enrich students’ knowledge. Keywords: Grammar in Spoken Siscourse, Need Analysis, Teaching Grammar